Analisis Kesuksesan Website E-Pelayanan Dinas Sosial Kota Surabaya Menggunakan Model DeLone McLean - Nurcahyani, Anisa; Safitri, Eristya Maya; Wulansari, Anita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The utilization of technology and information in government administration, especially through the concept of E-government, is the main focus to improve the efficiency and accessibility of public services in Indonesia. One of the cities implementing E-government is Surabaya city by developing an E-service website for the Social Service Office. The E-service website is designed to make it easier for citizens to apply for a poor certificate online. However, the implementation of E-government systems often faces obstacles in implementing services to users. This study uses the Delone-McLean Information System Success Model to evaluate the E-service website from the perspective of the Surabaya City community. Analysis of information quality, service, system, digital literacy, actual use, user satisfaction, and net benefits (E-government Performance) revealed that Service Quality, Digital Literacy, and System Quality have a positive and significant effect on actual use. Actual use, in turn, has a positive and significant impact on user satisfaction (User Satisfaction) and E-government performance. However, Information Quality shows a negative influence on user satisfaction and actual use. This research provides an understanding of the main factors that influence the successful implementation of E-government systems in Surabaya city and encourages further development efforts to improve service quality and its positive impact on society. Recommendations include improving the quality of information, services and systems to ensure the continuity and success of the E-government system in Surabaya City.